The Geography of Financial Misconduct - PARSONS, CHRISTOPHER A.; SULAEMAN, JOHAN; TITMAN, SHERIDAN (Journal of Finance, 2018)
ABSTRACT Financial misconduct (FM) rates differ widely between major U.S. cities, up to a factor of 3. Although spatial differences in enforcement and firm characteristics do not account for these patterns, city‐level norms appear to be very important. For example, FM rates are strongly related to other unethical behavior, involving politicians, doctors, and (potentially unfaithful) spouses, in the city.